Underpinning Theory Key Concepts, Practical Applications, and Future Prospects - Abu Hassim, Affendy; Sanusi Abd Manaf; Shamsudin, Mohd Farid (Asia Pacific Journal of Social Science Research, 2024)
Underpinning theory is the foundational framework for understanding and guiding research across various disciplines. It provides the theoretical basis for explaining complex phenomena and informs practical applications. This article explores the essential role of underpinning theory, its development and evolution, and its practical applications. It explores key theories such as the Health Belief Model, Resource-Based View, Constructivist Theory, Social Learning Theory, and Innovation Diffusion Theory, highlighting their successful implementation in real-world contexts. Additionally, the article addresses the challenges and limitations associated with underpinning theory, including theoretical evolution, empirical validation, and practical applicability. Future directions are also discussed, emphasising the need for interdisciplinary research, emerging technology integration, and inclusive theoretical framework development. By examining case studies and theoretical advancements, this article underscores the significance of underpinning theory in shaping effective research and practice.